Leveraging HR Analytics to Strengthen Strategic Workforce Planning and Talent Acquisition - Santoso, Dwi Putra; Priyanto, Sapto (Riwayat: Educational Journal of History and Humanities, 2025)
The relocation of Indonesia's capital city to the Archipelago Capital (IKN Ibu Kota Nusantara) in East Kalimantan has brought about a number of security challenges that need to be systematically addressed, even during the construction phase. Among these challenges, the threat of terrorism stands out, especially given the importance of the new capital as a national asset. This article aims to explore how to prevent terrorist attacks on the archipelago's capital by applying the principles of Crime Prevention Through Environmental Design (CPTED). Employing a qualitative research methodology, this study draws on a range of literature, including books, journals, and various sources. The concept of CPTED serves as the foundational framework for the analysis. The findings identify two main sources of potential terrorist threats in the new capital: firstly, cross-border terrorism and secondly, the vulnerability to attacks due to the fact that security and defense measures are predominantly concentrated in the surrounding buffer cities. To mitigate these risks, the research suggests several strategies for preventing terrorism, including enhancing access control through the deployment of security personnel, implementing comprehensive surveillance methods that integrate communication systems and visitor monitoring, and bolstering community engagement to foster a sense of territoriality among local residents.